Substance use among refugee adolescents: A systematic review from a public health perspective - Akyol Güner, Türkan (Addicta: The Turkish Journal on Addictions, 2026)
Refugee children and adolescents represent one of the most vulnerable populations in terms of health and psychosocial well-being due to exposure to war, forced displacement, family separation, poverty, discrimination, and acculturation-related stressors. This review aims to examine substance use among refugee adolescents within the context of migration from a public health perspective and to synthesize current empirical evidence on associated risk and protective factors. A systematic literature review of studies published between 2015 and 2024 was conducted using PubMed, Scopus, Web of Science, Google Scholar, and national Turkish databases. The review was conducted and reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. Eight empirical studies conducted in Türkiye, Australia, Sweden, Palestine, Jordan, and Serbia met the inclusion criteria. The findings indicate that, in a limited number of studies including direct comparisons, substance use among refugee adolescents tends to be higher than among their non-refugee peers. Tobacco use emerged as the most prevalent behavior, while alcohol and illicit substance use were more prominent in resettlement contexts characterized by acculturative stress. Key risk factors included trauma exposure, psychological distress, disrupted family functioning, peer influence, low socioeconomic status, and limited access to education and psychosocial support. Substance use frequently co-occurred with mental health problems such as anxiety, depression, and post-traumatic stress disorder, increasing vulnerability to violence, victimization, and other high-risk behaviors. Conversely, school connectedness, supportive family relationships, and social support networks functioned as important protective factors. Overall, the findings suggest that substance use among refugee adolescents should be conceptualized as a multidimensional public health concern shaped by the interaction of developmental sensitivity and displacement-related adversity. Culturally sensitive, community-based prevention and intervention strategies targeting refugee adolescents are urgently needed.